The Effect of Implementing HPC (Home Pharmacy Care) on Medication Adherence and Quality of Life in Chronic Diseases Patients with the Brief Counseling Method - Yusnita Yusnita; Lisma Luciana; Tuti Sahara (GLOBAL HEALTH SCIENCE GROUP, 2024)
People with chronic diseases who generally require long-term treatment tend to experience problems with non-adherence to their therapy. Non-compliance in taking medication can maintain the patient's condition and impact his quality of life. this research aims to determine the effectiveness of implementing hpc (home pharmacy care) on medication compliance and quality of life in chronic diseases patients using the brief counseling method. The research design is quasi experimental using a pre-test and post-test group design. This research was conducted from 11 June to 27 August 2024. The sample in the study was 33 respondents. The results of the Wilcoxon-Rank Test statistical test show that there is a difference in the level of medication compliance before and after receiving the home pharmacy care implementation intervention for respondents with a value of p-value = 0.00, and there is also a difference in the quality of life of respondents after receiving the home pharmacy care implementation intervention with p- value = 0.00 (p<0.05). The implementation of home pharmacy care, apart from being beneficial in increasing compliance with taking medication, also has an effect on improving the quality of life for chronic disease sufferers. Providing counseling education can increase sufferers' knowledge about drugs, the amount and function of prescribed drugs, as well as increase patient compliance behavior so that it has an impact on mortality and morbidity, as well as improving the quality of life of sufferers. It is hoped that respondents will remain adherent to the treatment regimen in order to improve their health and quality of life.